UJI AKTIVITAS ANTIMIKROBA HASIL BIOPRODUKSI KAPANG ENDOFIT DAUN LIDAH MERTUA (Sansevieria trifasciata Prain) - Lea P. Retnoningsih; Shirly Kumala; Marlin M. Raunsai; Partomuan Simanjuntak (PROSIDING SEMINAR KIMIA, 2022)
Secondary metabolite from Lidah mertua’s leaves (Sansevieria trifasciata Prain) had reported antimicrobial activity. The aim of this study is to determine the fractions of secondary metabolite produced by endophytic fungi of Lidah mertua’s leaves which potential to be antibacterial agent against Staphylococcus aureus and Escherichia coli. Rejuvenated endophytic fungi in Potato Dextrose Agar (PDA) fermented in Potato Dextrose Yeast (PDY) for 14 days, extracted with ethyl acetate obtained F.A and F.B extract from filtrat and B extract from biomass. F.A and B extract fractionated with coloumn chromatography ( SiO2; n-heksan – ethyl acetate and dichlorometana – methanol) obtained 8 fractions from filtrate extract (F.A-1 ~ F.A-8) and 5 fractions from biomass extract (B-1 ~ B-5). Anti-pathogenic bacterial tests used the KLT-bioautography dot-blot and elusion methods. Fraction F.A-1 ~ F.A-8 and F.B extract showed antimicrobial activity against S. aureus InaCC-B4 and E. coli InaCC-B5. Fraction B-1 ~ B-5 showed antimicrobial activity against S. aureus but the B-5 fraction were not showed antimicrobial activity againts E.coli. The fraction that has the potential to be a broad-spectrum antibacterial is the fraction F.B. Keywords: antimicrobial activity test, bioproduction, endophytic fungi, Lidah mertua’s leaves, Sansevieria trifasciata Prain.